Exploring molecular moieties on carbonized polymer dots from flavonoid glycosides with activity against enterovirus A71. (15th June 2022) - Lin, Chin-Jung; Unnikrishnan, Binesh; Lehman, Caitlin W.; Wang, Pei-Hua; Tseng, Yufeng Jane; Harroun, Scott G.; Lin, Shih-Chao; Huang, Chih-Ching
Abstract: In recent years, numerous reports have revealed that hesperetin (Hsp) and its glycoside form, hesperidin (Hsd), exhibit significant antioxidant, anti-inflammatory, antibacterial, and antiviral activities. However, high concentrations of Hsp or Hsd are required to achieve in vivo therapeutic efficacy, since the accompanying toxicity has limited their use practical applications. To enhance bioactivity while reducing the potential associated toxicity, we synthesized carbonized polymer dots (CPDs) from hesperetin (Hsp) or hesperidin (Hsd) via mild pyrolysis and compared their antiviral activities with those of their raw precursors against enterovirus A71 (EV-A71). Our results showed that while Hsp and Hsd exhibited limited antiviral activity to suppress EV-A71-induced cytotoxicity in rhabdomyosarcoma cells, the CPDs possessed excellent antiviral activity with median effective concentration values of 44.2 and 17.7 μg mL −1, respectively, demonstrating improved antiviral effects compared to Hsp and Hsd (each >200 μg mL −1 ). Hsd-CPDs showed superior inhibition of EV-A71 infection compared to Hsp-CPDs, as shown by the >8-fold higher selectivity index. Molecular docking further suggests that apocynin and guaiacol moieties on the surface of the Hsd-CPDs could bind to the hydrophobic pocket of viral protein 1 of EV-A71, thus inhibiting viral attachment. We also demonstrated that Hsd-CPDs exert multiple mechanisms, including blocking viral entry and suppressing oxidative stress that triggered viral replication and translation. More importantly, Hsd-CPDs substantially alleviate the clinical symptoms and reduce death rates associated with EV-A71 infection in neonatal mice. Our results reveal the superior therapeutic effects of Hsd-CPDs against EV-A71 could be a potential antiviral agent worthy of future clinical investigation. Graphical abstract: Image 1 Highlights: ● Mild pyrolysis-mediated carbonization of flavonoid glycosides leads to the formation of carbonized polymer dots (CPDs). ● The CPDs have dense bioactive moieties of guaiacol and apocynin on their surfaces. ● The CPDs exhibit superior biocompatibility and antiviral activity compared to their precursor molecules. ● The CPDs significantly reduce the death rates of EV-A71-infected neonatal mice.